(untitled) (Scientific journal of the Fergana State University, 2024)
The work studied changes in the total content of glycogen, salt-soluble proteins and total lipids by season and base, which was a continuation of the experience of quantitative changes in gas exchange and respiratory coefficient in winter and autumn.